Fractures: Forty year of DEF treatment. Alternativa for developing countries - Aybar Montoya, Alfredo (2020)
Objective: Show the evolution of limb fracture management with the Disposable External Fixation (FED) alternative.Currently there are a large number of internal and external devices for the treatment of these injuries, some, the most publicized, are expensive for our environment. The young doctor has the feeling, particularly in severe cases, that if he does not have them, they would not be in a position to cure them. Material and methods: The experiences of some classics of Orthopedics (1850) up to the experiences of current Schools (2020) are described, as well as, comparatively, our point of view with the method we call the DEF System. The how and why of healing broken bones are reviewed. Cases include fractures in diaphyseal, metaphyseal, and peri-articular areas of large bones, closed fractures, and open fractures even with bone loss and large wounds. Also the handling of complicated cases attributable to inadequate treatments. It is emphasized that only based on classifications, it is possible to estimate exact diagnoses, prognostic scopes and, proposals for treatment alternatives. Results: The most varied, complex cases, even with bone loss, were resolved competitively with the DEF System technique. Conclusions: For developing countries like ours, where foreign external fixation devices are expensive, the DEF System alternative is a simple and economical efficient management option.